2020
DOI: 10.1111/cge.13744
|View full text |Cite
|
Sign up to set email alerts
|

A novel homozygous variant in NLRP5 is associate with human early embryonic arrest in a consanguineous Chinese family

Abstract: Early embryonic arrest is one of the major causes of recurrent assisted reproduction failure. It is characterized by delayed embryonic development and failure to form viable eight‐cell stage embryos on day 3 of an assisted reproduction cycle. A recent study reported that biallelic mutations in NLRP5 can cause early embryonic arrest. NLRP5 is a member of subcortical maternal complex, which plays a significant role in embryogenesis. In this study, we described a female in a consanguineous Chinese family who disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
(24 reference statements)
1
15
0
Order By: Relevance
“…Additionally, KHDC3L , NLRP2 , NLRP5 , and NLRP7 variants were successively indicated to cause abnormal fertilization or embryonic arrest 9‐12 . However, there were no ZBED3 and OOEP related variants reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, KHDC3L , NLRP2 , NLRP5 , and NLRP7 variants were successively indicated to cause abnormal fertilization or embryonic arrest 9‐12 . However, there were no ZBED3 and OOEP related variants reported.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupting SCMC genes in mice causes embryonic arrest 5 . Variants in human SCMC genes are associated with embryonic arrest 6‐15 . However, these variants can account for failed pregnancies only a few patients.…”
Section: Introductionmentioning
confidence: 99%
“…Females carrying defective MEGs are healthy, but at risk of reproductive failure due to early developmental arrest or imprinting disorders of their offspring [31]. Recently, human genetic studies confirmed the involvement of several MEGs in reproductive disorders, including primary infertility due to preimplantation embryonic lethality [32][33][34][35][36]. Playing such important roles in embryo development, MEGs are potential targets of age-associated changes in aging oocytes.…”
Section: Expression Of Maternal Effect Genes In the Aging Oocytementioning
confidence: 99%
“…Various mechanisms leading to arrested development have been proposed coupled by numerous explanations on why these mechanisms may be instigated [ 9 ]. One of the most prominent theories views arrest as a protective mechanism for averting further development of poor-quality embryos [ 9 , 10 , 11 ]. Another hypothesis suggests that other than developmental arrest reflecting a predestined intrinsic scenario of natural selection processes where poor-quality embryos are “cut-off”, we should also consider the possibility that it is the demanding nature of reaching these milestones itself coupled by the respective in vitro culture laboratory conditions that play an important role in failure of embryos to reach these milestones and arrest [ 12 ].…”
Section: Introductionmentioning
confidence: 99%